A Research Synthesis of Quasi and Experimental Studies for Thai Elderly Health Promotion at Currently - Wongsaree, Chutchavarn; Panomrit, Surapan; Chaleoykitti, Saisamon; Promla, Walianaree; Phuksuknithiwat, Thanannipha; Charoenphong, Sudthicharat (Journal of health and health management, 2021)
This article aimed to synthesize knowledge for enhancing health care competence among Thai elderly. Using PICOD-T for systematic search and analysis, this paper synthesized nine (9) qualified researches as inputs. The analysis results found that: 1) Most health programs in the synthesized researches are comprised of mixed models that focus on developing knowledge; 2) Activities include giving advice and teaching knowledge in a structured and concrete manner (the pattern involves demonstration, practice of health promotion, follow-up and assessing health conditions, coaching on health promotion and involving family and friends in promoting health); 3) Technology and online media are tapped to promote health. 4) Results are measured before and after joining the program (which include knowledge, perception, behavior, clinical outcome indicators, quality of life, diet, physical performance, balance, sleep, brain function, psycho-emotional and psychosocial behavior); 5) Popular theories and concepts include: Pender's Health Promoting Theory, Health Belief Model Theory, Social Support Concept, Health Belief Model and Empowerment for Health Promotion; 6) The overall readiness of the body is assessed by monitoring blood pressure, pulse, sugar level, chest pain, exacerbation and other abnormalities during the program. Recommended to use Telenursing for Teaching knowledge and following up on self-health promotion behaviors of the elderly in the next normal.